MORPHOLOGY DEVELOPMENT AND CRYSTAL GROWTH IN NANOCRYSTALLINE AGGREGATES UNDER HYDROTHERMAL CONDITIONS: INSIGHTS FROM TITANIA - SIMULATIONS AND EXPERIMENTS - Penn R.L.; Banfield J.F. (My University, 1999)
High-resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD) peak broadening (Scherer) analysis were used to study coarsening and morphology development of nanocrystals. Experimental work used synthetic, equidimensional anatase (TiO2) particles about 5 nm in diameter. Under hydrothermal conditions (100-250°C, 15-40 bars), rapid growth occurs along [001], driven in part by the relatively high surface energy of (001) and in part by a kinetic effect involving a cyclic generation of highly reactive adsorption sites. Rapid growth along [001] depresses the <101> growth rate until (001) surfaces shrink to a critical cluster size. A second major coarsening mechanism significantly reduces the surface energy, especially under acidic conditions. This mechanism involves topotactic attachment of primary particles at high energy surfaces (most commonly {112}, less commonly (001)) and can result in elongate single crystals. Oriented attachment may be an important coarsening mechanism under a wide range of conditions encountered in the laboratory and in natural environments.